Anna Alexeyevna Radionchenko (to the 80th birthday) - Editorial Article (Бюллетень сибирской медицины, 2007)
Creative biography of the marked Russian scientist, obstetrist-gynecologist , corresponding member of RAMS, professor A.A. Radionchenko, who celebrates her 80-th anniversary.